Analyses of Paleozoic and Mesozoic brittle fractures in West-Finnmark. Geometry, kinematics and relations to structures on the Finnmark Platform in the southwestern Barents Sea - Bergø, Espen (UiT Norges arktiske universitet, 2016)
This study focuses on Paleozoic and Mesozoic brittle faults and fractures found onshore and offshore in the northwestern areas of Finnmark, the Finnmark Platform, and the southwestern Barents Sea Margin. These structures have been mapped using software for mapping (ArcGIS 10.5 & Petrel 2013) and analyzing fault-fracture lineaments and faults from bathymetry, digital elevation models, satellite images, aerial images, seismic data, and magnetic anomaly data. The main offshore features studied are the Troms Finnmark Fault Complex (TFFC), the Måsøy Fault Complex, Gjesvær Low, southern parts of Nordkapp Basin and the northern parts of Hammerfest basin. These record Mesozoic and Paleozoic faults, offsetting from the Mesozoic to the Precambrian strata. The Hammerfest- and Nordkapp Basins are bounded by NE-SW and NW-SE oriented faults. The onshore areas of the study area comprises Precambrian basement rocks and Caledonian allochthons occurring as a NE-SW trending belt extending from Magerøya in the northeast to the southwest into Troms County. The foliation and basements rocks are visible affected by brittle faults and fractures. Dominant strike directions on northwestern Porsanger Peninsula are NE-SW, NW-SE and E-W, while Magerøy records dominantly E-W. Directions are related to the TFFC directions. These faults and fractures manifest in outcrops, lineaments on aerial photos, DEM and bathymetry. The lineaments can be traced onshore to offshore. The landscape displays lineaments, fjords and sounds localized in high-density fracture zones, or in the core zones of major faults. The landscape indicates that there are several larger faults hidden in western Finnmark. The onshore NE-SW and E-W lineaments, faults and fractures can be compared with the offshore NE-SW to E-W faults. These NE-SW to E-W oriented faults, fractures and lineaments are related to the tensional stress from the opening of the Atlantic Ocean Margin. NW-SE oriented lineaments are presumed to be related to the Trollfjord Komagelv Fault Zone (TKFZ), ...